Genetic Diversity, Analysis of Some Agro-Morphological and Quality Traits, and Utilization of Plant Resources of Coriander (Coriandrum sativum) Supported with Cluster and Multivariate Analyses - Abdurrahman Basol; Gulsum Yaldiz; Mahmut Camlica (Biology)
In this study, 119 different coriander genotypes (38 different countries), including 114 genotypes and five cultivars, were undertaken to characterize the genotypes based on phenotypic, morphological, yield, and International Union for the Protection of New Varieties of Plants (UPOV) properties, along with some chemical properties. The yield components were between 1.34 and 21.49 g for thousand-grain weight, 0.02–9.58 g/plant for fruit yield, 0.01–50.78 g/plant for biological yield, and 8.48–73.36% for harvest index. Similarly, the results of this study revealed significant variations in essential oil (0.05–1.86%v/w) and fixed oil content (10.22–34.03%v/w). The main components of the essential oil were determined as linalool (3.13–45.70%v/v), p-cymene (0.10–15.77%v/v), ɣ-terpinene (0.04–13.80%v/v), while the fixed oil main acids were determined as petroselinic (24.47–87.70%v/v), palmitic (7.13–23.04%v/v), elaidic (1.55–47.44%v/v), and behenic acids (3.17–12.56%v/v). The cluster, heat map, correlation, and principal coordinate (PCA) analyses were conducted to determine the genetic diversity and relationship among the genotypes based on the examined properties. The cluster and heat map analyses showed differences in the same origin genotypes. Petroselinic acid was the major contributing factor for PCA. As a result of this study, Ames 13900 and Ames 18595 genotypes had high values for fruit yield, fixed oil content, and essential oil content.